2012
DOI: 10.1055/s-0039-3401675
|View full text |Cite
|
Sign up to set email alerts
|

Supra-scapular foramen in Indian dry scapulae

Abstract: Background and aims : Supra-scapular notch is roofed by superior transverse scapular ligament and converted into a foramen which provides passage for suprascapular nerve. When it is completely ossified that time it manifest as supra-scapular foramen in dry scapulae. Variations of superior transverse scapular ligament include calcification, partial or complete ossification and multiple bands. Presence of this foramen in dry scapulae is considered to be rare. Aim of the study was to verify the prevalence of supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Our study reported 4.1% incidence of completely ossified STSL which is close to the report of Dunkengrun et al [13] and Jadhav et al 2012 (10.57%) [14] was quite high as compared to our study. Complete ossification of STSL was very rare in some population such as in American Native 2.1-2.9 %, Eskimos-0.3% [15].…”
Section: Discussionsupporting
confidence: 91%
“…Our study reported 4.1% incidence of completely ossified STSL which is close to the report of Dunkengrun et al [13] and Jadhav et al 2012 (10.57%) [14] was quite high as compared to our study. Complete ossification of STSL was very rare in some population such as in American Native 2.1-2.9 %, Eskimos-0.3% [15].…”
Section: Discussionsupporting
confidence: 91%
“…The ossification of suprascapular ligament is multi factorial and from the literatures we found that its incidence varies from 1.36% to 30.76% in different populations of world. In present study, we found 13.33% incidence of ossified superior transverse scapular ligament which is nearer to findings of Jadhav et al [7] (10.57%). Silva et al [8] reported the incidence of completely ossified superior transverse scapular ligament 30.76% in Brazilian population which is very high as compared to our study.…”
Section: Discussionsupporting
confidence: 66%
“…Many researchers have recognized that the morphological variation of the suprascapular notch and the ossification of the STSL is the origin of suprascapular nerve entrapment syndrome [5][6][7][8][9]. The shape and size of the notch may be a reason in suprascapular nerve entrapment because narrow suprascapular notch have been found in patients with this syndrome [4,[10][11][12][13][14]. It is essential for clinical practice because a range of techniques are connected with the athroscopic decompression of the nerve [15].…”
mentioning
confidence: 99%